Answer:
Choice A
Step-by-step explanation:
Use the F. O. L. D method while solving
3x + 5 > 11
3x + (5 - 5) > 11 - 5
3x > 6
3x / 3 > 6 / 3
x > 2
x - 3 < 1
x (-3 + 3) < 1 + 3
x < 4
When subtracting / adding values to both sides, the inequality does not change.
When multiplying / dividing by a positive value, the inequality also doesn't change, but when multiplying , dividing with a negative value, the inequality must be flipped.
Answer:
![\cos x=\dfrac{8}{f}](https://tex.z-dn.net/?f=%5Ccos%20x%3D%5Cdfrac%7B8%7D%7Bf%7D)
Step-by-step explanation:
Given that,
![\tan x=\dfrac{e}{8}\\\\\sin x=\dfrac{e}{f}](https://tex.z-dn.net/?f=%5Ctan%20x%3D%5Cdfrac%7Be%7D%7B8%7D%5C%5C%5C%5C%5Csin%20x%3D%5Cdfrac%7Be%7D%7Bf%7D)
We need to find the value of cos x.
We know that,
![\tan\theta=\dfrac{\sin\theta}{\cos\theta}](https://tex.z-dn.net/?f=%5Ctan%5Ctheta%3D%5Cdfrac%7B%5Csin%5Ctheta%7D%7B%5Ccos%5Ctheta%7D)
Using the above relation,
![\dfrac{e}{8}=\dfrac{\dfrac{e}{f}}{\cos x}\\\\\cos x=\dfrac{\dfrac{e}{f}}{\dfrac{e}{8}}\\\\=\dfrac{e}{f}\times \dfrac{8}{e}\\\\=\dfrac{8}{f}](https://tex.z-dn.net/?f=%5Cdfrac%7Be%7D%7B8%7D%3D%5Cdfrac%7B%5Cdfrac%7Be%7D%7Bf%7D%7D%7B%5Ccos%20x%7D%5C%5C%5C%5C%5Ccos%20x%3D%5Cdfrac%7B%5Cdfrac%7Be%7D%7Bf%7D%7D%7B%5Cdfrac%7Be%7D%7B8%7D%7D%5C%5C%5C%5C%3D%5Cdfrac%7Be%7D%7Bf%7D%5Ctimes%20%5Cdfrac%7B8%7D%7Be%7D%5C%5C%5C%5C%3D%5Cdfrac%7B8%7D%7Bf%7D)
So, the value of cos x is equal to
.
Answer:
Step-by-step explanation:
2 × ( 3x + 6 )° + ( 16x + 14 )° = 180°
22x + 26 = 180
22x = 154
x = 7
<em>Note: Your question seems a little bit ambiguous. So, I am assuming the given function f(x)=9x+7.</em>
<em>Thus, I am solving based on it. It would still clear your concept. </em>
Answer:
The inverse of f(x)=9x+7
Step-by-step explanation:
Given the function
![f(x)=9 x + 7](https://tex.z-dn.net/?f=f%28x%29%3D9%20x%20%2B%207)
A function g is the inverse of function f if for y=f(x), x=g(y)
Replace x with y
![x=9y+7](https://tex.z-dn.net/?f=x%3D9y%2B7)
solve for y
![9y=x-7](https://tex.z-dn.net/?f=9y%3Dx-7)
![y=\:\frac{x-7}{9}](https://tex.z-dn.net/?f=y%3D%5C%3A%5Cfrac%7Bx-7%7D%7B9%7D)
Therefore,
The inverse of f(x)=9x+7 is:
i.e.
![\mathrm{Inverse\:of}\:9x+7:\quad \frac{x-7}{9}](https://tex.z-dn.net/?f=%5Cmathrm%7BInverse%5C%3Aof%7D%5C%3A9x%2B7%3A%5Cquad%20%5Cfrac%7Bx-7%7D%7B9%7D)